PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY - Noviyanti Anita Wulandari; Sumadi Sumadi; Yarmaidi Yarmaidi (JPG (Jurnal Penelitian Geografi), 2014)
This study aims to: (1) improve the learning activity, (2) improve learning outcomes.The method which was used was a classroom action research and the research subjects were students of class XI IPS 1 and the object of research was the Two Stay Two Stray type of Cooperative Learning model, learning activity and learning outcomes in geography class. Data collection techniques was done by observing and testing technique. Analysis of the data was done by using the percentage of student activity and percentage of students who can pass the study. The results from this research are: (1) the application of Cooperative Learning Model of type Two Stay Two Stray could improve learning activities, (2) the implementation of the Two Stay Two Stray type of Cooperative Learning could improve the students learning outcomes.Penelitian ini bertujuan untuk: (1) meningkatkan aktivitas belajar, (2) meningkatkan hasil belajar. Metode yang digunakan adalah penelitian tindakan kelas dengan subjek penelitian yaitu siswa kelas XI IPS 1 dan objek penelitiannya adalah model Cooperative Learning Tipe Two Stay Two Stray, aktivitas belajar dan hasil belajar geografi. Teknik pengumpulan data dengan teknik observasi dan teknik tes. Analisis data dengan menggunakan persentase aktivitas siswa dan persentase siswa tuntas belajar. Hasil penelitian menunjukkan bahwa: (1) penerapan model Cooperative Learning Tipe Two Stay Two Stray dapat meningkatkan aktivitas belajar, (2) penerapan model Cooperative Learning Tipe Two Stay Two Stray dapat meningkatkan hasil belajar siswa.Kata kunci: aktivitas belajar, hasil belajar, two stay two stray